Psychometric characteristics of core FertiQoL questionnaire in a Spanish sample of infertile women - Bueno-Sánchez, Lidia; Alhambra-Borrás, Tamara; Bonilla-Campos, Amparo; Durá-Ferrandis, Estrella (Anales de Psicología / Annals of Psychology, 2024)
Background: Fertility diagnosis and treatment have an impact on the quality of life (QoL) of individuals. FertiQoL is an internationally developed questionnaire to measure fertility-specific QoL. Obtaining reliable information on the impact of fertility issues enables social and health care systems to develop value-centered integrated care. Objective: The aim of the present study is to examine the dimensionality, validity and reliability of Core FertiQol in a sample of Spanish women undergoing fertility treatment. Methods: A cross-sectional study was conducted, administering the Core FertiQoL questionnaire to 564 women with fertility problems. Descriptive analyses were performed on sociodemographic and clinical data of the sample. The psychometric properties of the FertiQoL were tested by performing confirmatory factor analyses, calculating the average values of the variance extracted, validity, reliability and correlation coefficients between scales. Results: Four factors (Emotional, Mind/Body, Relational and Social) were obtained. All statistics presented adequate values (RMSEA and SRMR lower than 0.09 and CFI and TLI higher than 0.9). Reliability was demonstrated with the CR index of each factor higher than 0.7 and the AVE higher than 0.5. Conclusions: Core FertiQol presents an acceptable adjustment for Spanish women with fertility problems. It offers a communication channel between professionals and patients, as well as accurate information in its subscales on areas that may reflect QoL impairment. Core FertiQol is an instrument that allows the identification of areas requiring support, providing valuable information for the design of efficient social-health value-centered programs for people with infertility.